Disposable Bioreactors - Eibl, Regine; Eibl, Dieter (Advances in Biochemical Engineering/Biotechnology, 2010)
Over the past five years, the immense financial pressure on the development and manufacturing of biopharmaceuticals has resulted in the increasing use and acce- ance of disposables, which are discarded after harvest and therefore intended only for single use. In fact, such disposables are implemented in all the main bioprocess production stages today and an even higher growth than those in the biopharmac- tical market is predicted (reaching double figures). Alongside disposable filter capsules, membrane chromatography units, tubing, connectors, flexible containers processing or containing fluids, freezer systems, mixers and pumps, and fully c- trolled disposable bioreactors of up to 2,000 L culture volume are already available on the market. Numerous studies highlight the advantages of disposable bioreactors and reveal their potential for simple, safe and fast seed inoculum production, process devel- ment and small as well as middle volume production (e.g. bioactive substances, viruses for vaccines and gene therapies etc.). They suggest that such disposable bioreactors (typically characterized by the cultivation chamber or bag from plastic materials) may be advantageous for plant, animal and microbial cells. Running industrial activities such as CFD-modelling, development of single-use process monitoring and control technology, and standardized film formulations are attempting to resolve the limitations of the current disposable bioreactors. These achievements, along with substantial improvements in product yield, will reduce the use of stainless steel in the biomanufacturing facilities of the future.